THE CONSEQUENCES OF HUMANITARIAN PEACEKEEPING IN AFRICA - Ferreira, Rialize (Scientia Militaria - South African Journal of Military Studies, 2011)
Owing to the changing nature of international conflict, the 1990s witnessed a growing need for humanitarian peacekeeping operations, especially in Africa. The reluctance of the United Nations to be involved in peacekeeping operations in Africa compelled South Africa to take part in peacekeeping to assist neighbouring conflictridden states. There is, however, a discrepancy between the conceptualisation and application of peacekeeping and peace-enforcement operations. This notion is manifest in the changing nature of post-Cold War conflicts and requisite strategies, doctrines and operational procedures to execute these operations. A shift in South African defence policy was necessary to accommodate an expanded mandate to make provision for African peacekeeping missions. These humanitarian missions unfortunately also have unintended, latent consequences for the host populations, which can harm the peace operations as such. The aim of this article is to investigate traditional peacekeeping shifting to peace-building as a manifest, intended consequence and the way in which unintended, latent consequences of peacekeeping come about.